Answer:
x=0.66+1.88i
x=0.66-1.88i
Step-by-step explanation:
Given
3[tex]x^{2}[/tex]-4x+12=0
using the Quadratic Formula where
a = 3, b = -4, and c = 12
[tex]x=-b[/tex]±[tex]\sqrt{b^{2}-4ac } /2a\\[/tex]
x=-(-4)±[tex]\sqrt{(-4)^{2}-4(3)(12) } /2(3)[/tex]
x=4±[tex]\sqrt{16-144} /6[/tex]
x=-4±[tex]\sqrt{128} /6[/tex]
[tex]b^{2} -4ac<0\\[/tex]
x=-4±[tex]8\sqrt{2} i[/tex]/6
[tex]x=\frac{2}{3}[/tex]± [tex]\frac{4\sqrt{2}i }{3}[/tex]
Which becomes,
x=0.66+1.88i
x=0.66-1.88i
The value of x will be x=0.66+1.88i
x=0.66-1.88i